Efficacy and Safety of Concurrent Chemoradiotherapy Combined With Induction Chemotherapy or Adjuvant Chemotherapy in Patients With Stage II–IVA Nasopharyngeal Carcinoma: A Propensity Score Matching Analysis and Meta-Analysis - Jie Yang; Jie Yang; Zhong-Guo Liang; Yu-Ting Jiang; Kai-Hua Chen; Ling Li; Song Qu; Xiao-Dong Zhu; Xiao-Dong Zhu (Frontiers in Oncology, 2021)
PurposeTo evaluate the efficacy and safety of induction chemotherapy (IC) combined with concurrent chemoradiotherapy (CCRT) versus CCRT combined with adjuvant chemotherapy (AC) in patients with stage II–IVA nasopharyngeal carcinoma (NPC), we conducted a retrospective study and a meta-analysis combining the results of our studies.Patients and MethodsWe used the propensity score matching (PSM) to balance variables. A total of 168 patients were chosen by one-to-two PSM, including 101 patients with IC + CCRT and 67 cases with CCRT + AC. We used the Kaplan–Meier curve to compare survival outcomes and also used Cox regression analysis to determine independent prognostic factors. For meta-analysis, we determined the related studies by searching the PubMed database. We used STATA v12 software to perform meta-analysis of the extracted data and calculate pooled hazard ratios, 95% confidence intervals of survival outcomes, and risk ratios for the toxicities.ResultsIn this retrospective study, there was no significant difference in 5-year overall survival (76.9% vs. 79.0%, P = 0.966), progression-free survival (71.3% vs. 68.5%, P = 0.332), distant metastasis-free survival (80.5% vs. 74.2%, P = 0.140), and locoregional relapse-free survival (91.5% vs. 91.8%, P = 0.894) among patients with NPC with IC + CCRT versus CCRT + AC after PSM. For meta-analysis, six articles (including our study) reporting 1,052 cases of IC + CCRT and 883 cases of CCRT + AC were included in the meta-analysis. There was no difference of OS (pooled HR = 0.90, 95% CI: 0.63–1.29, P = 0.561), PFS (pooled HR = 1.07, 95% CI: 0.87–1.33, P = 0.633), DMFS (pooled HR= 0.98, 95% CI: 0.76-1.25, P=0.861), and LRRFS (pooled HR = 1.06, 95% CI: 0.76–1.48, P = 0.724).ConclusionThe efficacy of IC + CCRT and CCRT + AC was comparable in patients with stage II–IVA NPC. In terms of compliance and acute adverse reactions, IC + CCRT may be a potential therapeutic strategy.